Pilomatrixoma with Atypical Features: A Case Report - Meina Missak; Aaron Haig; Manal Gabril (Karger Publishers, 2021)
Pilomatrixoma is an uncommon, benign tumor with differentiation towards both the hair matrix and cells arising in the cortex, most frequently appearing in the first or second decade of life. In rare instances, pilomatrixomas can show malignant transformation. Pilomatrix carcinoma is extremely uncommon and has traditionally been considered a tumor of low malignant potential; however, a high local recurrence rate has been reported. There is a paucity of literature on these lesions, with only a few reports describing the spectrum of malignant changes seen in these lesions. In this case report, we present a case of pilomatrixoma in an adult patient showing atypical features. While the tumor is small, there are focal features that suggest progression to malignancy, but do not fulfill the criteria for pilomatrix carcinoma. These focal atypical features include a focal infiltrative pattern at the periphery, with a variable cytological atypia and an increased mitotic rate, up to five mitotic events/high-power field. Irregular foci of central necrosis (comedonecrosis) were present in several lobules. Some of the features identified were similar to a subset of pilomatrixoma, known as "proliferating pilomatrixoma." However, our case did not have the diffuse changes or larger size that has been frequently reported in "proliferating pilomatrixoma." In conclusion, given the lack of focality of the changes, the lesion in our case is best described as a pilomatricoma with atypical features. Furthermore, our case may highlight the need to ensure close clinical follow-up for these lesions with unexpected atypical features that raise concern of recurrence and malignant transformation.